2022
DOI: 10.3389/fimmu.2022.1060957
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic phenotype and immunosuppressive tumour microenvironment in pancreatic ductal adenocarcinoma: Key role of the urokinase plasminogen activator (PLAU)

Abstract: BackgroundPrevious studies have revealed the role of dysregulated urokinase plasminogen activator (encoded by PLAU) expression and activity in several pathways associated with cancer progression. However, systematic investigation into the association of PLAU expression with factors that modulate PDAC (pancreatic ductal adenocarcinoma) progression is lacking, such as those affecting stromal (pancreatic stellate cell, PSC)-cancer cell interactions, tumour immunity, PDAC subtypes and clinical outcomes from potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 136 publications
0
14
0
1
Order By: Relevance
“…PLAU encodes a secretory serine protease that converts plasminogen to plasminase 31 . PLAU has also been found to be involved in a variety of cancers and is associated with poor prognosis in a variety of cancers 32 ; Some experimental studies have proved that PLAU overexpression is associated with poor prognosis of PAAD, and plays an important role in PAAD resistance, invasion and migration 33 . However, the role of PLAU in the anoxia process of pancreatic cancer has not been well understood, and our study aims to fill this gap.…”
Section: Discussionmentioning
confidence: 99%
“…PLAU encodes a secretory serine protease that converts plasminogen to plasminase 31 . PLAU has also been found to be involved in a variety of cancers and is associated with poor prognosis in a variety of cancers 32 ; Some experimental studies have proved that PLAU overexpression is associated with poor prognosis of PAAD, and plays an important role in PAAD resistance, invasion and migration 33 . However, the role of PLAU in the anoxia process of pancreatic cancer has not been well understood, and our study aims to fill this gap.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In cancer cells, elevated NHE1 activity enhances malignant transformation, 14 invasion, and metastasis. 15,16 NHE1 has been implicated in cancer regulation, 17 progression, and metastasis of breast, 15,18−20 ovarian, 21,22 pancreatic, 23,24 gastric, 25 and prostate 26 cancers as well as hepatocellular carcinoma. 27 The existence of cation/H + exchangers was first proposed in 1961.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It controls the electroneutral exchange of a single intracellular H + for an extracellular Na + ion (1:1 stoichiometry) across the plasma membrane, acting to elevate intracellular pH (pH i ). NHE1 thus regulates Na + levels, pH i , cell volume, proliferation, and cell migration , and has been correlated with pathological conditions such as heart disease and hypertension. , In cancer cells, elevated NHE1 activity enhances malignant transformation, invasion, and metastasis. , NHE1 has been implicated in cancer regulation, progression, and metastasis of breast, , ovarian, , pancreatic, , gastric, and prostate cancers as well as hepatocellular carcinoma …”
Section: Introductionmentioning
confidence: 99%
“…33 The authors described pH-dependent inhibition of ASIC1 activity in Chinese Hamster Ovary (CHO) cells and demonstrated that the leads occupied an allosteric binding site within the extracellular PcTX1 domain through solution of a X-ray cocrystal complex with chicken ASIC1a (Protein Data Bank ID 6X9H). The aminoindazole lead 4-fluoro-6-((1-(5fluoro-2-methylpyridin-4-yl)azetidin-3-yl)oxy)-1H-indazol-3amine (13) showed potent activity against wild-type ASIC1 at pH 6.0 (WT IC 50 = 25 nM), with target engagement demonstrated by significant decreases in inhibition against heterologously expressed ASIC1 bearing single alanine substitutions at the putative binding site (F98A IC 50 = 746 We recently reported on the activity of two novel series of 6substituted amiloride 35 and 5-N,N-hexamethylene amiloride 28 analogs as inhibitors of urokinase plasminogen activator (uPA), a TLSP linked to cancer metastasis 36,37 rheumatoid arthritis, 38 and other inflammatory diseases. 39,40 Lead inhibitors from these efforts showed low nanomolar uPA potency, high target selectivity across the serine hydrolase superfamily, loss of unwanted ENaC activity, low hERG activity, and in vivo antimetastatic effects in xenografted mouse models of lung and pancreatic cancer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We recently reported on the activity of two novel series of 6-substituted amiloride and 5- N , N -hexamethylene amiloride analogs as inhibitors of urokinase plasminogen activator (uPA), a TLSP linked to cancer metastasis , rheumatoid arthritis, and other inflammatory diseases. , Lead inhibitors from these efforts showed low nanomolar uPA potency, high target selectivity across the serine hydrolase superfamily, loss of unwanted ENaC activity, low hERG activity, and in vivo antimetastatic effects in xenografted mouse models of lung and pancreatic cancer. ,, In this study, we characterize the structure–activity relationships of compounds from these series and related amiloride derivatives as inhibitors of proton-activated currents mediated by ASICs using automated patch clamp electrophysiology, identify an analog with improved potency, and test its potential as pharmacological tool to probe endogenous human and rodent ASIC function.…”
Section: Introductionmentioning
confidence: 99%